ANASLISIS KESULITAN BELAJAR PESERTA DIDIK DALAM MEMAHAMI MATERI SEJARAH DI KELAS XI IPS - Evi Ariani Astri; Maria Ulfah; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to determine the difficulties as well as internal and external factors that affect learning difficulties of students in the history subject of class XI IPS at SMAN 1 Sungai Raya. The research method used is descriptive research. The subject of this study was 6 students who had difficulty in learning history and 1 history teacher of class XI IPS. The data collection techniques was observation, intervews and decomentations. The result shows that the difficulties faced by the students relate to academic problems such as hard to pay attention to the teacher, hyperactivy, often sleepy, did not apply good learning and there were some studentswho make noise, the internal factors that affect students learning difficultiesin were the health of the students that interferes with learning, lack of intelligency, lack of interest and readiness to learn history. And external factors that affect learning difficulties of students were less attention of parents to student’s learning, teacher use a tradtional methods learning and less various strategic learning, lack of discipline and students disrupt the teaching learning process .Keywords: Learning Difficulties Factors, Learning Process, Historical Subjects.